Enhancing Food Safety Measures in Micro Small Medium Enterprises: A Comprehensive Analysis of MSMEs in Kemiling Bandar Lampung - Kasuma, Achmad Bintang Herida (CV. Lenggogeni Data Publishing, 2024)
MSMEs in the food business, especially in Indonesia, encounter major obstacles in adhering to food safety requirements because of their restricted resources and technical knowledge. This study investigates the effects of applying Hazard Analysis and Critical Control Points (HACCP) methodology on enhancing food safety standards at a particular MSME, Desi Kue, situated in Bandar Lampung, Indonesia. The study uses surveys, interviews, and hazard analysis assessments to identify potential dangers and suggest effective management techniques to improve food safety processes at Desi Kue. Customized education and training programs are crucial for enhancing awareness and comprehension of food safety among MSME stakeholders. The report emphasizes the importance of adjusting food safety policies and resources to tackle the specific difficulties encountered by MSMEs. MSMEs can effectively adopt HACCP principles by working with regulatory organizations and industry associations. This will help improve consumer trust, ensure public health, and promote sustainable growth in the food sector. This study offers significant insights for Desi Kue and MSMEs in Indonesia and other developing countries, enabling them to capitalize on prospects for competitiveness and growth in the global market by implementing strong food safety management systems.